2019
DOI: 10.1097/j.pain.0000000000001561
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone relates to enhanced incisional acute pain and pinprick hyperalgesia in the luteal phase of female volunteers

Abstract: The role of sex hormones on postsurgical pain perception is basically unclear. Here, we studied the role of endogenous gonadal hormones for pain and hyperalgesia in human volunteers after experimental incision. A 4-mm incision was made in the volar forearm of 15 female volunteers both in the follicular and the luteal phase (random block design). Somatosensory profiles were assessed at baseline and 1 to 72 hours after incision by quantitative sensory testing, compared between both cycle phases, and related to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 92 publications
4
22
0
Order By: Relevance
“…Moreover, Piroli et al have shown that healthy young women exhibit lower postoperative pain sensitivity by undergoing gynecological laparoscopy in the follicular phase compared with that in the luteal phase 9) . Furthermore, results of the present study agree with recent findings that pinprick evoked pain, incision-induced pain, and mechanical hyperalgesia were significantly greater during the luteal phase compared to the follicular phase in female volunteers 10) . Moreover, the VAS scores of pain intensity, in relation to the pain threshold, were not significantly different between the two phases in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, Piroli et al have shown that healthy young women exhibit lower postoperative pain sensitivity by undergoing gynecological laparoscopy in the follicular phase compared with that in the luteal phase 9) . Furthermore, results of the present study agree with recent findings that pinprick evoked pain, incision-induced pain, and mechanical hyperalgesia were significantly greater during the luteal phase compared to the follicular phase in female volunteers 10) . Moreover, the VAS scores of pain intensity, in relation to the pain threshold, were not significantly different between the two phases in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…The model did not entail brush allodynia. In women, both the intensity and extent of hyperalgesia were found sensitive to the hormonal phases (Pogatzki‐Zahn et al., 2019 ). Systemic lidocaine previous to incision prevented 2HA, while neither subcutaneous nor systemic lidocaine reverted hyperalgesia once it was fully developed (Kawamata, Takahashi, et al., 2002 ; Kawamata, Watanabe, et al., 2002 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is acknowledged that factors such as race/ethnicity, sex (e.g. phases of menstrual cycle [65]) and age could influence pain sensitivity [66,67], but considering that we measured reliability of pain sensitivity in a single session rather than pain sensitivity per se, the effect of these factors on our results remain limited. Future studies must be conducted in chronic pain participants, such as chronic low back pain.…”
Section: Methodological Considerationsmentioning
confidence: 98%